Are poor people conditionally cooperative? Contrasting evidence from a field-adapted contributions game - Allen IV, James; Karachiwalla, Naureen; Rakshit, Deboleena (International Food Policy Research Institute, 2025)
We study conditional cooperation using a field-adapted conditional contributions game in rural Mozambique, eliciting community members’ willingness to contribute to a new public program conditional on how many others contribute. While past studies suggest most people are conditional cooperators (contributing more as others do), most of our sample (57%) are undefined by standard classifications. Instead, our sample's most common types are largely absent from the literature: counter conditional cooperators (contributing less as others do) and v-shaped cooperators, both for monetary donations (30% and 19%) and volunteering (35% and 12%). Our findings motivate future research in both non-laboratory and low-income settings.